2008
DOI: 10.1088/0004-637x/690/1/l76
|View full text |Cite
|
Sign up to set email alerts
|

The Dust-to-Gas Ratio in the Small Magellanic Cloud Tail

Abstract: The Tail region of the Small Magellanic Cloud (SMC) was imaged using the MIPS instrument on the Spitzer Space Telescope as part of the SAGE-SMC Spitzer Legacy. Diffuse infrared emission from dust was detected in all the MIPS bands. The Tail gas-to-dust ratio was measured to be 1200 ± 350 using the MIPS observations combined with existing IRAS and H i observations. This gas-to-dust ratio is higher than the expected 500-800 from the known Tail metallicity indicating possible destruction of dust grains. Two clust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 40 publications
8
57
0
Order By: Relevance
“…Bendo et al (2010) also compare radial variations in the D/G with the oxygen abundance gradients and found a good correspondence, although the D/G radial variations seems to be steeper. Recent studies in the low-metallicity Magellanic Clouds have shown that their D/G are lower than that estimated for more metal-rich environments (Bernard et al 2008;Gordon et al 2009), consistent with what should be expected from the previous relation between the D/G and the metallicity. James et al (2002), using JCMT/SCUBA observations at 850 μm observations, concluded that the fraction of metals incorporated into dust was a universal constant, that is to say similar for dwarf and giant galaxies, which was in contradiction to the Lisenfeld & Ferrara (1998) conclusions.…”
Section: Introductionsupporting
confidence: 75%
“…Bendo et al (2010) also compare radial variations in the D/G with the oxygen abundance gradients and found a good correspondence, although the D/G radial variations seems to be steeper. Recent studies in the low-metallicity Magellanic Clouds have shown that their D/G are lower than that estimated for more metal-rich environments (Bernard et al 2008;Gordon et al 2009), consistent with what should be expected from the previous relation between the D/G and the metallicity. James et al (2002), using JCMT/SCUBA observations at 850 μm observations, concluded that the fraction of metals incorporated into dust was a universal constant, that is to say similar for dwarf and giant galaxies, which was in contradiction to the Lisenfeld & Ferrara (1998) conclusions.…”
Section: Introductionsupporting
confidence: 75%
“…This is the same time at which the SMC tail, a tail of tidal origin located within the Bridge, was stripped from the galaxy (Gordon et al 2009). This means that if the Bridge material were stripped earlier, it did not form stars.…”
Section: Dynamics and The Magellanic Bridgementioning
confidence: 83%
“…The large magellanic cloud (LMC) is a late-type spiral galaxy seen nearly face-on, rich in gas and with active star formation while the small magellanic cloud (SMC) is a highly inclined irregular galaxy with less active star formation. Their dynamical interaction is claimed to be responsible for the various star forming episodes and of the creation of the Magellanic Bridge, connecting the two galaxies, (Gordon et al 2009) and the Stream (Nidever et al 2008). The LMC is probably just a few kpc thick, along the line of sight, but the SMC has a more complex structure that may extend up to 20 kpc.…”
Section: Introductionmentioning
confidence: 99%
“…In order to quantify in a more objective way the detection of these three structures we followed the approach adopted by Gordon et al (2009) who, to this aim, used the correlation expected between hydrogen column density and foreground subtracted FIR maps. We have looked for such correlations in regions E, F and G, between the high resolution hydrogen map, and SPIRE images.…”
Section: Far-infrared Structuresmentioning
confidence: 99%